Endotoxin-inactivating activity in normal and pathological human blood samples. - Obayashi, T (1986)
The endotoxin-specific chromogenic test revealed that plasma endotoxin-inactivating activity was markedly diminished by endotoxemia, but not by fungemia or by dialysis with cellulose membranes, suggesting that fungal polysaccharides and other nonendotoxic, Limulus-reactive materials do not consume endotoxin-inactivating factors in the blood. There was a close negative correlation between plasma endotoxin concentration and endotoxin-inactivating activity. The specificity of the test was improved by fractionating amebocyte lysate and using only the factors that constitute the endotoxin-sensitive coagulation pathway of the horseshoe crab. This test was able to differentiate endotoxemia from fungemia and from contamination with other nonendotoxic, Limulus-reactive materials.